Efektivitas Metode Pembelajaran Scramble dalam Meningkatkan Hasil Belajar Geografi di SMAN 1 Enam Lingkung - Aprianti, Meri; Nofrion, Nofrion (TSAQOFAH, 2025)
Geography learning is often perceived as difficult by students due to its broad scope and the limited variety of teaching methods employed, which can reduce students' concentration during classroom instruction. This study aims to analyze the effectiveness of the Scramble learning method in improving the geography learning outcomes of Grade XI students at SMAN 1 Enam Lingkung. A quantitative approach with a quasi-experimental design was used, involving two classes of 32 students each. Data were collected through observation, testing, and documentation, and analyzed statistically. The results show that the calculated t value of 2.70 exceeds the critical t value of 1.99 at the 5% significance level (α = 0.05), indicating acceptance of the alternative hypothesis. Additionally, the n-gain scores reveal an improvement of 0.71 (high category) in the experimental class and 0.55 (moderate category) in the control class. These findings demonstrate that the Scramble learning method is effective in enhancing students' geography learning outcomes. The study concludes that innovative teaching methods are essential for improving students' conceptual understanding and academic performance. The implications encourage educators to adopt more interactive and engaging instructional strategies to foster a more effective learning environment.